Functional Deletion/Insertion Promoter Variants in SCARB1 Associated With Increased Susceptibility to Lipid Profile Abnormalities and Coronary Heart Disease - Hu, Senlin; Hu, Dong; Wei, Haoran; Li, Shi-yang; Wang, Dong; Li, Chen-ze; Jiang, Jiangang; Wang, Daowen; Cui, Guanglin; Wang, Daowu (Frontiers in Cardiovascular Medicine, 2022)
Background: Genetic variants in Scavenger receptor Class B Type 1 (SCARB1) influencing high-density lipoprotein cholesterol (HDL-C) and coronary heart disease (CHD) risk were identified by recent genome-wide association studies. Further study of potential functional variants in SCARB1 may provide new ideas of the complicated relationship between HDL-C and CHD. Methods: 2000 bp in SCARB1 promoter region was re-sequenced in 168 participants with extremely high plasma HDL-C and 400 control subjects. Putative risk alleles were identified using bioinformatics analysis and reporter-gene assays. Two indel variants, rs144334493 and rs557348251, respectively, were genotyped in 5,002 CHD patients and 5,175 control subjects. The underlying mechanisms were investigated. Results: Through resequencing, 27 genetic variants were identified. Results of genotyping in 5,002 CHD patients and 5,175 control subjects revealed that rs144334493 and rs557348251 were significantly associated with increased risk of CHD [odds ratio (OR): 1.28, 95% confidence interval (CI): 1.09 to 1.52, p = 0.003; OR: 2.65, 95% CI: 1.66–4.24, p = 4.4 × 10−5). Subsequent mechanism experiments demonstrated that rs144334493 deletion allele attenuated forkhead box A1 (FOXA1) binding to the promoter region of SCARB1, while FOXA1 overexpression reversely increased SR-BI expression. Conclusion: Genetic variants in SCARB1 promoter region significantly associated with the plasma lipid levels by affecting SR-BI expression and contribute to the susceptibility of CHD.